2015
DOI: 10.1177/1368430214561694
|View full text |Cite
|
Sign up to set email alerts
|

The effect of resource competition on Blacks’ and Asians’ social distance using a virtual world methodology

Abstract: In this study we used a virtual world to examine the effects of resource competition on dynamic social distance between Blacks and Asians, 1 and both minority groups in relation to a dominant White majority in the U.S. context. The literature indicates that Blacks and Asians experience greater social distance from one another relative to each group's social distance towards Whites (e.g., Smith, Bowman, & Hsu, 2007;Weaver, 2008). Group threat theory of intergroup relations (Blumer, 1958) offers one possible exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 48 publications
5
26
0
Order By: Relevance
“…As regards the practical implications of our findings, the results clearly show that the national majority group has the power to shape interminority relations. Moreover, they corroborate earlier results which point out that relative status not only to the majority group but to also other minority groups in society is an important factor in interminority relations (see Tawa et al, 2013;Tawa et al, 2015). Thus, both future research and practical interventions should better acknowledge the role of national majorities in supporting the formation of positive interminority relations.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…As regards the practical implications of our findings, the results clearly show that the national majority group has the power to shape interminority relations. Moreover, they corroborate earlier results which point out that relative status not only to the majority group but to also other minority groups in society is an important factor in interminority relations (see Tawa et al, 2013;Tawa et al, 2015). Thus, both future research and practical interventions should better acknowledge the role of national majorities in supporting the formation of positive interminority relations.…”
Section: Discussionsupporting
confidence: 86%
“…Schalk-Soekar et al, 2004), these similarities are not solely responsible for status differences. The role of the multidimensionality of social space and the relativeness of group power in intergroup SECONDARY TRANSFER EFFECT AMONG IMMIGRANTS relations has recently been brought up by Tawa and his colleagues (Tawa, Suyemoto, & Tauriac, 2013;Tawa, Negrón, Suyemoto, & Carter, 2015) in their studies in the US context conducted among Black, Asian and White Americans. The authors showed that, instead of approaching interminority relations as vertical, that is, reflecting the groups' positions in ethnic hierarchy, we need to acknowledge that different minority groups experience power and privilege relative to one another, and both relative to the dominant majority.…”
Section: Public Collective Self-esteemmentioning
confidence: 99%
“…Nevertheless, a growing body of research in the virtual world such as the current analysis are increasingly supporting the validity of the virtual world method by demonstrating that behaviors in virtual worlds frequently correspond to real-world behaviors (Bayraktar and Amca 2012;Blascovich et al 2002;Bailenson et al 2008;Feldon and Kafai 2008;Lee and Park 2011;Lo 2008;Tawa et al 2015;. Findings from our preliminary analyses also contribute to the validity of virtual worlds as analogues of real life; for example, we found that on average, both non-US-born participants and women tended to have closer interpersonal distances to peers than USborn participants and men, and these patterns of cultural and gender differences in interactions resemble findings from well-established previous research in the real world (Evans and Howard 1973).…”
Section: Discussionmentioning
confidence: 95%
“…Various studies about human behaviors have been conducted in virtual worlds supporting the validity of virtual worlds for intergroup behavioral research (Bayraktar and Amca 2012;Blascovich et al 2002;Bailenson et al 2008;Feldon and Kafai 2008;Lee and Park 2011;Lo 2008;Rizzo and Schultheis 2002;Tawa et al 2012aTawa et al , 2015Tippett et al 2009;Ward and Sonneborn 2009;). For example, Lee and Park (2011) examined whether social contingency theory was applicable within Second Life (SL).…”
Section: Methodsmentioning
confidence: 98%
“…SL was not developed for research, but social scientists soon recognized its utility as a platform to study human interaction. A number of the studies conducted have tended to focus on examining the unique characteristics of SL participants (Hooi & Cho, 2014;McLeod, Liu, & Axline 2014), the behavior of SL avatars in virtual worlds (Grinberg, Careaga, Mehl, & O'Connor, 2014;Hooi & Cho, 2013), the use of SL for online instruction within educational institutions (Halvorson, Ewing, & Windisch, 2011;Inman, Wright, & Hartman, 2010), or the feasibility of conducting social experiments and experimental manipulations in SL (Greiner, Caravella, & Roth, 2014;Lee, 2014;Tawa, Negrón, Suyemoto, & Carter, 2015). A handful of studies have used SL as a tool for recruitment, though generally the recruitment goals are directed at specific populations (Keelan et al, 2015;Swicegood & Haque 2015).…”
Section: Discussionmentioning
confidence: 99%